Nature and Occurrence of Lexical Bundles in Mathematical Lesson Plans as Indicators of Authority Relationships - Gandhi, Haneet; Mittal, Ruchi (JOURNAL OF INDIAN EDUCATION, 2021)
This study draws on authority structures that were observed in mathematics lesson plans developed by pre-service teachers during their internship period. Language clues, in the form of lexical bundles, were identified and categorised as an indication of authority structures. Four categories of authority structures were found to be present in the mathematics lesson plans, viz., personal authority, discourse as authority, discursive inevitability and personal latitude; among these, personal authority and discourse as authority appeared most pervasive. It was also found that pre-service teachers’ beliefs evolved during their internship period. Towards the end of their school experience programme, their beliefs towards authority structures changed as by then they had started sharing authority with their students.